Antioxidant potential of an anthraquinone metabolite isolated from a marine fungus. - Vidal-Valenzuela, Isabel; Torres-Vargas, José Antonio; García-Caballero, Melissa; Medina-Torres, Miguel Ángel; Rodríguez-Quesada, Ana María (My University, 2023)
Marine ecosystem is a fruitful source of many pharmacologically active. In particular, a number of marine anthraquinones and their derivatives, have been studied for their potential as anticancer and antimetastatic agents, although little is known about their antiangiogenic activities. In addition, there is some controversy regarding the poor antioxidant effect of these marine secondary metabolites. In this study, we describe for the first time the antiangiogenic activity of an anthraquinone, isolated from a marine fungus, which was evidenced in vitro by the inhibition of the activated endothelial cells survival, proliferation, and differentiation into tubelike structures. Furthermore, we have demonstrated its protective effect against reactive oxygen species (ROS), especially in presence of hydrogen peroxide, a potent prooxidant agent. These results were evidenced by a reduced ROS production and an increased redox capacity of cells after treatment with this anthraquinone, evidenced through the staining with DCFHDA and the sulfhydryl groups determination, respectively. The observation that this compound appears to present a more potent effect in tumor than in endothelial cells, suggests a putative selectivity. All these results highlight the need for further study of this molecule as a potential therapeutic agent for cancer and other angiogenesisdependent diseases.
Keywords: Hongos marinos - Uso terapéutico - Efectividad; Cáncer - Tratamiento; Danthron; Angiogénesis